Review on Breast Cancer in Iraq Women - Jassim, Marwa Mohammed Ali; Hamad, Bushra Jabbar; Hussein, Murtada Hafedh (University of Thi-Qar Journal of Science, 2022)
breast cancer" which is common type of carcinogenesis in females, surpassing even bronchogenic cancer "accounting for approximately one-third of the registered female cancers according to the latest Iraqi Cancer Registry". According to "World Health Organization", that discovery as well as examination early, particularly in combination together with sufficient therapy, present the appropriate method which decrease in the mortality rate for "breast cancer". Rate of "breast cancer" rise in Iraq, a source of a significant health problem. Labors are necessary on the nationalist scale and establishing comprehensive breast cancer control programs in Iraq for better estimate of the problem